4q-(7q+10)=6-(5q-5)

Simple and best practice solution for 4q-(7q+10)=6-(5q-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4q-(7q+10)=6-(5q-5) equation:


Simplifying
4q + -1(7q + 10) = 6 + -1(5q + -5)

Reorder the terms:
4q + -1(10 + 7q) = 6 + -1(5q + -5)
4q + (10 * -1 + 7q * -1) = 6 + -1(5q + -5)
4q + (-10 + -7q) = 6 + -1(5q + -5)

Reorder the terms:
-10 + 4q + -7q = 6 + -1(5q + -5)

Combine like terms: 4q + -7q = -3q
-10 + -3q = 6 + -1(5q + -5)

Reorder the terms:
-10 + -3q = 6 + -1(-5 + 5q)
-10 + -3q = 6 + (-5 * -1 + 5q * -1)
-10 + -3q = 6 + (5 + -5q)

Combine like terms: 6 + 5 = 11
-10 + -3q = 11 + -5q

Solving
-10 + -3q = 11 + -5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '5q' to each side of the equation.
-10 + -3q + 5q = 11 + -5q + 5q

Combine like terms: -3q + 5q = 2q
-10 + 2q = 11 + -5q + 5q

Combine like terms: -5q + 5q = 0
-10 + 2q = 11 + 0
-10 + 2q = 11

Add '10' to each side of the equation.
-10 + 10 + 2q = 11 + 10

Combine like terms: -10 + 10 = 0
0 + 2q = 11 + 10
2q = 11 + 10

Combine like terms: 11 + 10 = 21
2q = 21

Divide each side by '2'.
q = 10.5

Simplifying
q = 10.5

See similar equations:

| n-8=21 | | (2X+3)(5X+4)=20 | | 7x-9=-9x-7 | | 2-3(x-7)=1 | | 6(n-6)+7n=-140 | | x^1/3=4/3 | | 8x=-3+1 | | 2000+100h=1800+150h | | 1100+800+4z=700+300+7z | | 0.6x+4.3=3.4 | | 2y=-5y-24 | | (8x^4+3x^3-5)-(2x^2-6x+5)= | | 22-16=x | | 2(x+3)-1=3 | | 7/n=4/8 | | 6(4z-1)-3(z+6)=13(z+1) | | k-1/3=10 | | 4(-6)(-5)-2(-5)(2)= | | 2/5x-12=2 | | 6x+6y+6=0 | | 3*6-12/6 | | x-3/8=1x/3 | | 4x+6=4x-5 | | 6y+18=y+11 | | [[24]/[56]] | | 78=5t-7 | | -7(8x-7)+8(1+5x)=-23 | | 1-2x=3x-11 | | x-3/8=1-x/3 | | 3m+5=25 | | (20a^2b)/(4a^2b2) | | x(x)+3x-10=-6 |

Equations solver categories